Optical sensor system for time-resolved quantification of methane concentrations: Validation measurements in a rapid compression machine. (May 2018) - Bauke, Stephan; Golibrzuch, Kai; Wackerbarth, Hainer; Fendt, Peter; Zigan, Lars; Seefeldt, Stefan; Thiele, Olaf; Berg, Thomas
Highlights: A refined data analysis procedure for a methane sensor system capable of measuring temperature and gas concentration simultaneously inside an internal combustion engine is presented. The measurement method is based on broadband infrared absorption an calculations using the HITRAN database. Validation experiments under well-defined conditions using a rapid compression machine to simulate environmental conditions inside an internal combustion engine are performed. The determination of temperature is compared to a commercially available system based on water absorption in the near infrared. Accuracy and precision of the methane sensor system in determination of air-fuel ratios are 4.6% and 1.3%, respectively. Abstract: Lowering greenhouse gas emissions is one of the most challenging demands of today's society. Especially, the automotive industry struggles with the development of more efficient internal combustion (IC) engines. As an alternative to conventional fuels, methane has the potential for a significant emission reduction. In methane fuelled engines, the process of mixture formation, which determines the properties of combustion after ignition, differs significantly from gasoline and diesel engines and needs to be understood and controlled in order to develop engines with high efficiency. This work demonstrates the development of a gas sensing system that can serve as a diagnostic tool for measuring crank-angle resolved relative air–fuel ratios in methane-fuelled near-production IC engines. By application of non-dispersive infrared absorption spectroscopy at two distinct spectral regions in the ν3 absorption band of methane around 3.3 µm, the system is able to determine fuel density and temperature simultaneously. A modified spark plug probe allows for straightforward application at engine test stations. Here, the application of the detection system in a rapid compression machine is presented, which enables validation and characterization of the system on well-defined gas mixtures under engine-like dynamic conditions. In extension to a recent proof-of-principle study, a refined data analysis procedure is introduced that allows the correction of artefacts originating from mechanical distortions of the sensor probe. In addition, the measured temperatures are compared to data obtained with a commercially available system based on the spectrally resolved detection of water absorption in the near infrared.